The emergence of semantics in four linguistic traditions : Hebrew, Sanskrit, Greek, Arabic - Bekkum, Wout Jac. van (John Benjamins, 1997)
The aim of this study is a comparative analysis of the role of semantics in the linguistic theory of four grammatical traditions, Sanskrit, Hebrew, Greek, Arabic. If one compares the organization of linguistic theory in various grammatical traditions, it soon turns out that there are marked differences in the way they define the place of 'semantics' within the theory. In some traditions, semantics is formally excluded from linguistic theory, and linguists do not express any opinion as to the relationship between syntactic and semantic analysis. In other traditions, the whole basis of linguisti.
Keywords: Bible. -- Old Testament -- Criticism, interpretation, etc., Jewish.; Bible. -- Ancien Testament -- Critique, interprétation, etc. juives.; Bible. -- Old Testament; Rabbinical literature -- History and criticism.; Hebrew language -- Semantics.; Sanskrit language -- Semantics.; Greek language -- Semantics.; Arabic language -- Semantics.; Semantics, Comparative.; Littérature rabbinique -- Histoire et critique.; Hébreu (Langue) -- Sémantique.; Sanscrit (Langue) -- Sémantique.; Grec (Langue) -- Sémantique.; Arabe (Langue) -- Sémantique.; Sémantique comparée.; Arabic language -- Semantics; Greek language -- Semantics; Hebrew language -- Semantics; Rabbinical literature; Sanskrit language -- Semantics; Semantics, Comparative; Semantik; Semantiek.; Hebreeuws.; Sanskriet.; Grieks.; Arabisch.; Sanskrit.; Griechisch.; Hebräisch.; Criticism, interpretation, etc.